Histopatologia de Scomberomorus cavalla Cuvier 1829 (Perciformes: Scombridae) como biomarcador de la contaminación acuática - Reyes Márquez, Alejandra (Universidad Autónoma Metropolitana, 2018)
In the environmental monitoring it has been pointed out the importance of using histopathological scoring system protocols to determine environmental stress. Therefore, the aim of this study was to evaluate semi-quantitatively the histopathological changes in the liver, gills and muscle of the fish Scomberomorus cavalla to determine the health status of the organisms. The study was conducted in Tecolutla, Veracruz, Mexico. The organs analyzed were included in paraffin, cut (5 μm) and stained with H-E. A total of 63 slates (N = 7) were analyzed under an optical microscope. A modified version of the quantitative histological protocol described by Bernet et al. (1999) was used to evaluate target organs. Every alteration was assigned an importance factor and a score value based on the percentage of occurrence. The histopathological analysis reveals that the reference categories that presented greater relevance in the organs analyzed were circulatory disturbances and progressive changes in the liver (melanomacrophage centers) and gill (hyperplasia and lamellar fusion). The health diagnosis evaluated from the health indexes corresponds to organisms with normal tissue and structure, as well as the presence of moderate histopathological alterations. According to the scale of semiquantitative assessment, the lesion rates estimated in the present work correspond to poorly contaminated water, hence histopathological analysis can be a useful biomarker in the evaluation of aquatic contamination.; En el monitoreo de la contaminación acuática, se han propuesto protocolos histopatológicos que integran los efectos adversos a contaminantes como indicadores de la calidad del ambiente. En este trabajo se evaluó semicuantitativamente los cambios histopatológicos en el hígado, branquias y músculo de Scomberomorus cavalla a través de índices de lesión para la determinación del estado de salud. Se aplicó la escala de valoración semicuantitativa de daño tisular y se calcularon los índices de lesión descritos por Bernet et al. (1999). El análisis histopatológico, revela que las categorías de referencia que presentaron mayor relevancia en los órganos analizados fueron disturbios circulatorios y cambios progresivos en el hígado (centros melanomacrófagos) y branquia (hiperplasia y fusión lamelar). El diagnóstico de salud evaluado a partir de los índices de lesión corresponde a organismos con tejido y estructura normal, así como presencia de moderadas alteraciones histopatológicas. De acuerdo a la escala de valoración semicuantitativa de daño tisular, los índices de lesión estimados en el presente trabajo corresponden a aguas poco contaminadas, por lo cual el análisis histopatológico puede ser un biomarcador útil en la evaluación de la contaminación acuática.